Guidelines for Improving the Process of the Receiving and Put away Parcel for Dormitory of Chakri Naruebodindra Medical Institute - Nisa, Namfon; Meesisan, Pharanya; Kanthong, Darin; Sriboonruang, Wiranpat; Fuangprayoon, Tamonwan; Duangsuwarn, Vasurat (Journal for Strategy and Enterprise Competitiveness, 2024)
The Chakri Naruebodindra Medical Institute, Faculty of Medicine Ramathibodi Hospital, Mahidol University is a state educational institution and hospital with dormitories for staff and medical students to support their work and daily life. The institute has developed various information systems for efficient management. However, the process of receiving and put away parcels is still inefficient, causing delays in picking and delivering parcels to the staff and medical students. This study proposes a new approach to improving the parcel receiving and storage process by adding steps for sorting and storing parcels on shelves according to the alphabetical order of the recipient’s name. This reorganization aims to enhance orderliness and ease of parcel searching. The expected outcomes include reduced time for picking and delivering parcels, improved work efficiency and convenience for the parcel storage staff, increased convenience and speed in receiving parcels for the staff and medical students.